Allogeneic tumor rejection induced by the intravenous injection of Lyt- 2+ cytolytic T lymphocyte clones (The Rockefeller University Press, 1982)
The in vivo activity of murine Lyt-2+ cytolytic T lymphocyte clones was assessed in a tumor allograft model system. Mice that had been sublethally irradiated 16 h previously were injected intraperitoneally with 131I-IUdR-labeled tumor cells. Simultaneously, various doses of four cytolytic T cell clones were injected intravenously and the mice monitored for tumor cell elimination by whole-body counting tecniques. These four clones had been selected on the basis of their ability to proliferate in response to alloantigens in the absence of added T cell growth factor(s). With two of the four clones tested, rapid elimination of tumor cells within the peritoneal cavity was observed, as early as 48 h after intravenous injection of the cloned T cells.